Prevalence and Risk Factors for Minor Hallucinations in Patients with Parkinson’s Disease - Min Zhong; Ruxin Gu; Sha Zhu; Yu Bai; Zhuang Wu; Xu Jiang; Bo Shen; Jun Zhu; Yang Pan; Jun Yan; Li Zhang (Behavioural Neurology, 2021)
Purpose. As the most frequent and earliest type of psychotic phenomenon in Parkinson’s disease (PD), minor hallucination (MH) can occur before the onset of motor symptoms. This sensation may be an early predictor of severe psychotic and cognitive states and is often overlooked in clinics. This study was aimed at providing a comprehensive and in-depth understanding of MHs. Patients and Methods. Demographic information was obtained from 262 patients with PD, and a series of clinical assessment questionnaires were provided. According to the result of the Movement Disorders Society Unified Parkinson’s Disease Rating Scale Part I, the patients were classified into the MH and nonhallucination (NH) groups. Results. MHs were the most common psychotic symptom with 38.9% prevalence. The most frequent MH was visual illusion, especially object misidentification. Three minor phenomena were somewhat consistent in terms of external factors, temporal factors, and content. Disease duration, daily levodopa equivalent dose, and percentage of levodopa and dopamine-receptor agonist use were remarkably greater in the MH group than in the NH group. After covariate control, the MH group had worse life quality and more severe nonmotor symptoms, including poor sleep quality and rapid eye movement sleep behavior disorder (RBD), than the NH group. The binary logistic regression model showed that RBD, sleep quality, and health-related life quality were associated with MHs. Conclusion. A high prevalence of MHs was observed in patients with PD. Further studies are needed to confirm and expand the identified clinical factors related to MH, which have potential prognostic and therapeutic implication.